Peran Kepemimpinan Yayasan dalam Mengembangkan Lembaga Pendidikan Islam di MA AT-Taufiq Bogem Grogol Diwek Jombang - Hani Adi Wijono (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
The role of the foundation's leader is one of the keys between the foundation and the educational institution effectively, because it must pay attention to what happens in every development activity in the institution and the mission of the institution. The leader of the foundation is demanded to continually foster and enhance good cooperative relations with the institution in order to realize the mission of an effective and efficient institution. Institutional programs certainly cannot run smoothly if there is no support from a foundation. This study aims to determine the role of foundation leaders in the development of educational institutions. The place of research was conducted at MA At-taufiq Bogem. Grogol, Diwek, Jombang. The results showed that the foundation's leaders helped determine the policies and regulations of the institution, motivated the work of the head of the institution, strengthened all policies in the institution, played an active role in every institutional facility development, supervised and controlled every institution's activities, attended every board meeting the teacher to see all the problems and developments, hold a period of deliberation with the head of the institution to see the results of the institution's development report, conduct teacher training through monthly meetings, participate in educating teachers and students with santri status in each study filled with the foundation's own leaders who also as caregivers at the foundation's boarding school.